Biomechanical Comparison of Single-Bundle and Double-Bundle Posterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-Analysis. Issue 10 (October 2017) - Lee, Dong-Yeong; Kim, Dong-Hee; Kim, Hyun-Jung; Nam, Dae-Cheol; Park, Jin-Sung; Hwang, Sun-Chul
Abstract : Background: Of the many issues regarding surgical techniques for posterior cruciate ligament (PCL) reconstruction, the choice between single-bundle (SB) and double-bundle (DB) reconstruction is one of the most debated. However, it is unclear which of the reconstruction techniques yields better outcomes in knees with a PCL injury. The purpose of this meta-analysis was to compare the benefits of SB and DB PCL reconstruction in terms of biomechanical outcomes. Methods: The MEDLINE, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, and SCOPUS electronic databases were searched for relevant articles comparing the outcomes of SB and DB PCL reconstruction that were published up until August 2016. Data searching, extraction, analysis, and quality assessment were performed on the basis of the Cochrane Collaboration guidelines. Biomechanical outcomes of both techniques were evaluated using various outcomes. Results involving continuous outcomes are presented as standardized mean differences (SMDs) with 95% confidence intervals (CIs). Results: Ten biomechanical studies were included. There were no significant biomechanical differences between the groups with respect to external rotation, varus rotation, or coupled external rotation of the tibia with posterior drawer force at any knee flexion angle. However, posterior laxity measured using the posterior drawer test showed significantly better results after DB compared with SB reconstruction at low flexion (SMD = −0.90, 95% CI = −1.24 to −0.56, I 2 = 0%), 30° (SMD = −0.79, 95% CI = −1.28 to −0.31, I 2 = 48%), 60° (SMD = −0.87, 95% CI = −1.33 to −0.40, I 2 = 33%), and 90° (SMD = −0.73, 95% CI = −1.11 to −0.35, I 2 = 27%). Conclusions: Anatomic DB reconstruction of the PCL is superior to anatomic SB reconstruction in terms of restoration of anteroposterior stability. However, it remains unclear which technique yields better improvement in terms of external rotation laxity, varus laxity, and coupled external rotation of the tibia with posterior drawer force. High-quality randomized controlled trials are required to confirm and expand on these results.